The other side of a magic mirror: exploring collegiality in student and staff partnership work. Issue 5 (4th July 2021) - Scoles, Jenny; Huxham, Mark; Sinclair, Kelda; Lewis, Caroline; Jung, Julia; Dougall, Eoghen
ABSTRACT : This article adds to the corpus of writing that examines collegiality's idealistic yet elusive nature in Higher Education by focusing specifically on how collegiality can be enacted in student–staff partnership work. An innovative initiative, 'Students as Colleagues in the Review of Teaching Practices', provides a case to qualitatively explore the collegial characteristics. Here, students reviewed a paired staff member's teaching practice over one semester, as a peer review exercise. This shift in social roles troubles the understanding of 'peer' and asks if authentic collegiality is possible. The study is conceptually framed by Fielding's notion of 'radical collegiality' and draws on standpoint theory and dialogic education to raise issues of power, mutual support and productive tensions. The findings have implications for how Higher Education institutions can support student and staff to actively engage in authentic collegial partnerships by developing relational and dialogic spaces, rather than just abstract institutional infrastructures.